PROGNOSIS OF THE DEVELOPMENT OF ORTHOSTATIC HYPOTENSION IN YOUNG MALES WITH HYPERTENSION - Bilovol, Oleksandr Mykolaiovych; Kniazkova, Iryna Ivanivna; Bogun, Maryna Vadymivna (Medicinski časopis, 2020)
The aim of the study was to improve the prognosis of orthostatic hypotension (OH) in young males with hypertension (AH) during antihypertensive therapy. Materials and methods. 62 male patients were examined, mean age 31.5 ± 3.6 years with AH of the 1st and 2nd degrees. The control group consisted of 20 practically healthy persons (mean age 31.0 ± 3.7 years). All patients underwent general clinical examination, measurement of office blood pressure (BP), daily monitoring of BP with the help of the ABPM-02 device (Meditech, Hungary), active orthostatic test (AOT) with determination of the Kerdo vegetative index (KI). During AOT, ECG and heart rate variability (HRV) were monitored according to the conventional methodology using monitors CardioTens-01 («Meditech», Hungary). All patients underwent antihypertensive therapy In 80.6% of patients, AH was controlled with drugs. Results. The incidence of OH in patients with AH was 17.7% and did not differ significantly from the control group – 15%. Patients with AH showed a decrease of the degree of parasympathetic effect according to KI data, while in the control group KI became positive. It was found that at baseline, in the subgroup of young males with AH and OH in the orthostatic test, the spectral indices of HRV (LF and total power of the spectrum) were significantly lower than in patients with AH and negative orthostatic trial. Analysis of the dynamics of the HRV spectral indices during AOT showed that no significant changes were detected in the subgroup of patients with AH and OH. Therefore, in the course of AOT, absence of changes in HRV parameters in patients with AH confirms the presence of autonomic dysfunction and dysfunction of the autonomic supply, and also allows to predict the development of OH. Conclusion. Thus, prognosis of the development of OH in case of AH in young patients will allow more effective correction of BP in the specified cohort of patients.